Biochemical characterization of the minimal domains of an iterative eukaryotic polyketide synthase - Sabatini, Martín (2018)
Fil: Fil: Sabatini, Martín. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Biología Molecular y Celular de Rosario (IBR-CONICET); Argentina.